Diagnosis of a Severe Dust Storm Event over Iraq - Al-Dabbagh, Sama K. (Al-Mustansiriyah Journal of Science, 2025)
Background: Iraq experienced a severe dust event that occurred in mid-May 2022, disrupting daily life with adverse health impacts. Objective: This study aims to investigate the triggering weather systems, and examine the variations in meteorological factors during the event with a specific focus on Basrah station in southern Iraq. Methods: Ground-based meteorological observations and satellite imagery. In addition to the atmospheric composition forecast data from the copernicus atmosphere monitoring service (CAMS), including meteorological and optical properties for different levels. Applying statistical evaluations for CAMS data against observed data, including correlation coefficients, coefficient of determination, and error metrics (MBE and MAE). Results: The dust event was driven by a deep upper air cut-off low over the eastern Mediterranean region, coinciding with a southern intrusion of the polar jet stream. This situation led to baroclinic instability and the developing frontal cyclonic system over southern Turkey, Syria, Jordan, western Iraq to northern Saudi Arabia. Satellite images showed dense dust clouds swept and transported towards the east and southeast due to the front passage, which is simulated well in the CAMS model with a value exceeding 2.5 of optical depth. In Basrah station, the dust event led to a notable reduction in visibility, lower temperature by 4° C, and surface solar radiation of 15%. Wind speed, extinction coefficient, and humidity levels increase by about 2.2, 2, and 1.4 times respectively. 12% reduction in boundary layer height during daytime hours of a dust event, and an 8% increment during nighttime. The statistical assessment shows a strong correlation for temperature and humidity, moderate for wind speed, and weak for wind direction. The model overestimates temperature and wind direction, while underestimating humidity and wind speed. Errors are low for most variables but notably higher for wind direction. Conclusions: The May 2022 dust event was driven by a deep frontal cyclone, reaching central and southern Iraq, in which Basrah station witnessed reduced visibility, lower temperature and solar radiation, and increased wind speed, humidity, and extinction coefficient. Boundary layer height decreased during the day and rose at night, highlighting the atmospheric instability during the event.